Utilization of ChicoryWaste Flour and Cabbage Fermented by Rhyzhopus sp. in DietForGouramy (Osphronemus gouramy) Fry - Samuel Sitorus; Sitorus Sitorus; Indra Suharman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstrakThis research was carried out for 56 days in September-November 2018 in PT. Perkebunan Nusantara V, Panam, Pekanbaru. The aim of this research was to determine the effect of soybean meal (SM) substitution withfermentedchicorywaste flourand cabbage (FCWFAC) on feed digestibility, feed efficiency and growth of gouramy. The research uses a completely randomized design (CRD) with one factor, five treatment and three replications. The treatment was P0 (100% SM: 0% FCWFAC), P1 (90% SM:0%FCWFAC), P2 (80% SM:20%FCWFAC), P3 (70% SM:30%FCWFAC) and P4 (60% SM:40%FCWFAC). Crude protein content of tested diet was 30%. The result of this research showed the best treatment is P4 (60% SM:40%FCWFAC) with feed digestibility 69%, feed efficiency 28,82% protein retention 30,61% and specific growth rate 2,5%. Keywords :ChicoryWaste Flour and Cabbage,Fermentation, (Osphronemus gouramy).